Peran Pembiayaan Arrum Pegadaian Syariah terhadap Pengembangan Usaha Mikro di Banjarmasin - Mochammad Arif Budiman; Dewi Indah Astuti (STES Islamic Village, 2020)
Arrum is a loan scheme from Sharia Pawnshops aimed at micro-businesses in the community. The purpose of this study was to determine the role of Arrum financing in the Sultan Adam Banjarmasin Syariah Pawnshop Unit in the development of micro-businesses. The type of this research is field research using a qualitative approach, while the data is obtained by observation and interview methods. The results showed that Arrum financing contributed to the development of micro-businesses by increasing business capital, number of customers, and operating income. The implication of this research is that the Sultan Adam Banjarmasin Sharia Pawnshop Unit needs to continue to expand Arrum's financing products, improve promotion and service quality.